EVACUATION POLICY OF THE SOVIET GOVERNMENT TO TURKESTAN (American Journal of Interdisciplinary Research and Development, 2024)
In the 20s of the 20th century, this article describes the evacuation of the starving population of the famine-stricken regions of Russia to the Turkestan ASSR and their resettlement, provision of food, clothing and other supplies. Also, on the basis of archival materials and scientific literature, the aid provided by the state to the starving people evacuated to our country and the good deeds of the tolerant Turkestan population to the resettled peoples, as well as the reasons and processes of the Soviet government's evacuation of the starving people to Turkestan were analyzed and an objective solution was obtained.